Length–weight relationships for 37 freshwater fish species of Iran. (3rd April 2014) - Esmaeili, H. R.; Gholamifard, A.; Vatandoust, S.; Sayyadzadeh, G.; Zare, R.; Babaei, S.
Summary Length–weight parameters were estimated for 37 freshwater fish species of Iran belonging to seven families. Significant length–weight relationships with high correlation coefficients were found for all species.